PENGARUH PEMBERIAN VINASSE DAN SUMBER NITROGEN TERHADAP PERTUMBUHAN DAN HASIL WIJEN (Sesamum indicum L.) DI TANAH PASIR - , REAN AFINA, Ir. Sri Muhartini, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Sesame is dry land crop which has a high economic value in Indonesia. Planting sesame at sandy coastal land is an effort to increase sesame production. This research was aimed to study the effect of vinasse and nitrogen sources application on sandy soil to sesame growth and yield. The research has been done from May until September 2012 at Karangnongko, Maguwoharjo, Sleman. Treatments consisted of two factors arranged in completely randomized design. The first factor was vinasse dosage which consisted of five level, 0 l/ha, 25.000 l/ha, 50.000 l/ha, 75.000 l/ha, and 100.000 l/ha. The second factor was nitrogen sources ie, organic fertilizer, inorganic fertilizer, and without fertilizer. High dosage of vinasse which is 75.000 l/ha and 100.000 l/ha improved roots volume, plant height, and total dry weight. Cow dung application improved soil moisture levels, total soil nitrogen, roots volume, leaf area, number of leaf, plant height, total dry weight, number of pod, pod length, and yield. Combination vinasse and cow dung application improved soil moisture levels, leaf area, total dry weight, and oil seed content. Vinasse and cow dung could be used as organic nitrogen sources for sandy soil.